Small schools and the pressure to consolidate. - Howley, Aimee; Howley, Craig (Education Policy Analysis Archives, 2006)
Positioned in relationship to reform literature calling for small schools “by design” and interpreting data from a case study of a high performing but low-SES district in a Midwestern state, this paper provides a basis for making sense of the apparent divergence in policies governing schooling structures in rural and urban places. Its interpretation examines the way educational reformers work to valorize a multidimensional set of practices constituting “small school reform.” This reform package is, ironically, to some extent unrelated to what is actually taking place naturally in small schools and districts, where more “traditional” practices are said to be more common. Reformers often regard such practices as deficient, but that judgment seems to disregard empirical findings about school and district size, which typically show that smaller scale itself confers advantages across locales. Moreover, they overlook dynamics such as those revealed in this case study, which demonstrate how smaller scale promotes a close-knit family atmosphere as well as shared commitment to a set of core values. In addition, with smaller scale come structural arrangements that support an ethos of self-sufficiency and openness to “outsiders”—transient as well as open-enrollment students. These dynamics enable a small district to weather substantial threats to its existence.